(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides theoretical and practical justification for the person-centered approach model aimed at developing socio-communicative competence in future teachers. The research considers the personal characteristics of students preparing for the teaching profession, their skills in effective communication with the social environment, information exchange and active participation in collective cooperation as the main criteria. Through a person-centered approach, teaching methods appropriate to individual needs and opportunities are proposed in the educational process, and psychological and pedagogical conditions that positively affect the development of competence are highlighted. Based on the results of the research, a pedagogical model is developed that serves to form a communicative culture of future teachers, develop openness and empathy in mutual communication.